Comparison of Serum Copper, Zinc, Lead, Aluminium and Iron Levels in Patients with Parkinson’s Disease with Healthy Controls in Tertiary Care Hospital - Asad, Tahir; Aamir, Muhammad; Haroon, Zujaja Hina; Munir, Muhammad Usman; Kirmani, Sobia Irum; Awan, Afshan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare serum Copper, Zinc, Lead, Aluminium and Iron levels in patients with Parkinson’s disease with healthy subjects and the association of these trace elements. Study Design: Comparative Cross-sectional study. Place and Duration of Study: Department of Chemical Pathology and Endocrinology at Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Nov 2019 to Jul 2020. Methodology: Out of the total of 129 study participants, 83 were Parkinson’s disease patients, and 46 were healthy subjects. Serum Iron level was measured on random access fully automated chemistry analyser advia 1800. In addition, Copper, Zinc, Lead and Aluminium were measured by atomic absorption spectrophotometry. These levels were compared between patients with Parkinson’s disease and healthy subjects using the Mann-Whitney U test. Results: Out of the total 129 subjects, males accounted for 51(61.4%) and females were 32(38.6%) in the diseased Group, while in healthy subjects, males accounted for 22(47.8%) and females for 24(52.2%). Levels of Copper, Zinc and Iron were signifi-cantly decreased in patients with Parkinson’s disease compared to healthy subjects (p<0.001). However, serum concentrations of Aluminium and Lead showed an increasing trend in patients with Parkinson’s disease compared to age-matched healthy subjects (p<0.001). Conclusion: Decreased levels of serum copper, iron and Zinc were seen in patients with Parkinson’s disease, while aluminium and lead levels were raised, showing the potential neurotoxic role of these elements.